Annealing induced discoloration of transparent YAG ceramics using divalent additives in solid-state reaction sintering. Issue 13 (October 2017) - Zhou, Tianyuan; Zhang, Le; Selim, Farida A.; Sun, Rong; Wong, Chingping; Chen, Hao; Zhang, Qitu
Abstract: Tetraethyl orthosilicate (TEOS) was commonly served as a sintering additive to promote the densification of transparent Y3 Al5 O12 (YAG) ceramics. However, Si 4+ that decomposed from TEOS would restrain the conversion of dopants into a higher valence state (e.g., Cr 3+  → Cr 4+ ). In this study, by using divalent sintering additives (CaO and MgO), the colorless and highly transparent YAG ceramics (T = 84.6%, at 1064 nm) were obtained after vacuum sintering at 1840 °C for 8 h and without subsequent annealing in air. An absorption peak centered at ∼320 nm was observed before annealing, and it extended to ∼550 nm after annealing at 1450 °C for 10 h in air. A discoloration phenomenon occurred and more scattering centers were observed with the formation of new [Mg/Ca 2+ F + ] color centers. Air annealing did not improve the optical quality of the as-fabricated YAG ceramics with divalent dopants as sintering additives, owing to the formation of scattering centers.